Ð˜Ð·Ð¼ÐµÐ½ÐµÐ½Ð¸Ñ ÑÑ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ñ‹ ÑÐ½Ð° Ñƒ ÐºÑ€Ñ‹Ñ Ð¿Ð¾ÑÐ»Ðµ Ð¸ÑÐºÑƒÑÑÑ‚Ð²ÐµÐ½Ð½Ð¾Ð³Ð¾ Ð³Ð¸Ð¿Ð¾Ð¼ÐµÑ‚Ð°Ð±Ð¾Ð»Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ ÑÐ¾ÑÑ‚Ð¾ÑÐ½Ð¸Ñ - Shilo, A. V.; Ventskovska, O. A.; Babiychuk, G. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2010)
The influence of artificial hypometabolic state (AHMS) on slow wave sleep (SWS) and paradoxical sleep (PS) occurrence and their daily distribution was studied. Awaking from AHMS was accompanied by total sleep deprivation with the following compensatory increase in SWS and PS amounts. Moreover AHMS caused no prolonged or stable changes in the sleep-wake cycle and did not effect daily total sleep duration. Sleep structure and sleep cyclicity were restored within 24 hrs.